Quantum correlations and the explanatory power of radical metaphysical hypotheses. - Emery, Nina (Philosophical Studies, 2022)
I argue that, in at least one important sense, the hypothesis that you are a brain in a vat provides better explanations than the explanations provided by standard ways of interpreting our best scientific theories. This puts pressure on anyone who—like me!—wishes to resist taking this radical hypothesis seriously when doing science and scientifically-informed metaphysics. Insofar as our resistance is justified, it can't be justified simply by claiming that the brain in a vast hypothesis is explanatorily impoverished.